1976
DOI: 10.3171/jns.1976.45.2.0223
|View full text |Cite
|
Sign up to set email alerts
|

Pineal apoplexy associated with anticoagulant therapy

Abstract: A case is presented with the acute development of a pineal region syndrome secondary to hemorrhage into a pineal cyst in a patient who was under anticoagulant therapy. Resolution of the symptoms and signs followed excision of the lesion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
3

Year Published

1979
1979
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 23 publications
(1 reference statement)
0
22
0
3
Order By: Relevance
“…Old and recent areas of hemorrhage were identified microscopically in the resected pineal cyst of a patient with pineal apoplexy (23). The release of the debris accumulated by a single or recurrent intracystic hemorrhage seems to be able to cause meningitis with polymorphonuclear CSF pleocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…Old and recent areas of hemorrhage were identified microscopically in the resected pineal cyst of a patient with pineal apoplexy (23). The release of the debris accumulated by a single or recurrent intracystic hemorrhage seems to be able to cause meningitis with polymorphonuclear CSF pleocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…It may be associated with an increased likelihood of symptomatic presentation, 5,19,20,49,58,63 and sudden death from pineal hemorrhage with acute hydrocephalus has been reported. 41,55 Fleege et al 20 found fluid-fluid levels consistent with previous hemorrhage in 3 of 19 patients who presented with symptomatic pineal cysts.…”
Section: Discussionmentioning
confidence: 99%
“…Porém, já foi descrita hemorragia intracisto provocando efeito expansivo e compressão da lâmina quadrigeminal 17 .…”
Section: Fig 3 Cisto Pineal (õ) Em Corte Coronal T1 Antes (A) E Apósunclassified